Diagnosis and detection of VicK gene in Streptococcus mutans isolated from the saliva of patients with diabetic type 2 with tooth decay in the Iraqi population - Al-Sudani, Susan F.Khadhem; Hamad, Laheeb R.; Ali, Fattma A. (Cellular and Molecular Biology, 2022)
Type 2 diabetes mellitus (T2DM) is gradually becoming more common in Iraq. Salivary changes and proliferation of specific bacterial communities cause oral disease that can adversely affect systemic conditions such as diabetes. Fifty saliva samples were collected from people with T2DM suffering from tooth decay and twenty-five people without T2DM suffering from tooth decay. The periodontal status, the extent of the root surface, and coronal caries were evaluated. Saliva was cultured for investigating Streptococcus mutans. The results showed that patients with type 2 diabetes had significantly more severe Periodontitis and a higher prevalence and magnitude of bacterial caries. Diabetic subjects had higher levels of Hemoglobin A1c (HbA1c) and Random Blood Sugar (R.B.S.). The S. mutans diagnosis by PCR for Sanger Sequencing technique by using VicK gene sequences (1300bp). The PCR products of the isolate were submitted to Macrogen Company for sequencing. Selected seven isolates as new isolates registered in global gene bank as locally S. Mutans isolates in Bagdad city/Iraq and their accepted accession numbers include LOCUS MT603520, MT603521, MT603522, MT603523, MT603524, MT603525,and MT603526 of nucleotide sequence. The VicK genes isolates' phylogenetic trees revealed a genotype that was closely connected to other isolates in GenBank. Furthermore, gene sequencing demonstrated a success rate of 99 percent. resemblance to other isolates in the GenBank database The likelihood of a link between S. Mutans and dental carries was determined by these findings.